Laser-induced spatially-selective tailoring of high-index dielectric metasurfaces - Berzins, Jonas; Indrisiunas, Simonas; Fasold, Stefan; Steinert, Michael; Zukovskaja, Olga; Cialla-May, Dana; Gecys, Paulius; Baumer, Stefan M. B.; Pertsch, Thomas; Setzpfandt, Frank (Optics Express, 2020)
Optically resonant high-index dielectric metasurfaces featuring Mie-type electric and magnetic resonances are usually fabricated by means of planar technologies, which limit the degrees of freedom in tunability and scalability of the fabricated systems. Therefore, we propose a complimentary post-processing technique based on ultrashort (≤ 10 ps) laser pulses. The process involves thermal effects: crystallization and reshaping, while the heat is localized by a high-precision positioning of the focused laser beam. Moreover, for the first time, the resonant behavior of dielectric metasurface elements is exploited to engineer a specific absorption profile, which leads to a spatially-selective heating and a customized modification. Such technique has the potential to reduce the complexity in the fabrication of non-uniform metasurface-based optical elements. Two distinct cases, a spatial pixelation of a large-scale metasurface and a height modification of metasurface elements, are explicitly demonstrated.
CRIS-Team Scopus Importer:2023-04-20